(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2024)
The rise of international terrorism has underscored the critical need to combat terrorist financing, an essential element for the sustainability of global terrorist networks. This research examines the evolving framework of international law addressing the financing of terrorism, with a focus on the creation of new norms that may constitute customary international law. By analyzing key international instruments such as the International Convention for the Suppression of the Financing of Terrorism and the Financial Action Task Force’s (FATF) Special Recommendations, the paper explores how global cooperation and regulatory frameworks have developed to curtail terrorist financing. The research highlights the effectiveness of measures like know-your-customer (KYC) processes, suspicious transaction reporting (STR), and financial sanctions. It also critiques gaps in the existing legal regime, such as the under-regulation of alternative remittance systems and cryptocurrency use. Through a doctrinal methodology, this paper assesses whether international initiatives have successfully created binding global norms to suppress terrorist financing and considers the role of global bodies like the FATF in enforcing these standards.